Politics of Public Opinion : Local Councils and People's Assemblies in Korea, 1567-1894 - Ingeol, Kim, (Asian Studies E-Books Online, Collection 2025., 2025)
Eugene Y. Park's annotated translation of a long-awaited book by Kim Ingeol introduces Anglophone readers to a path-breaking scholarship on the widening social base of political actors who shaped "public opinion" ( kongnon ) in early modern Korea. Initially limited to high officials, the articulators of public opinion as the state and elites recognized grew in number to include mid-level civil officials, State Confucian College students, all Confucian literati ( yurim ), influential commoners who took over local councils ( hyanghoe ), and the general population. Marshaling evidence from a wealth of documents, Kim presents a compelling case for the indigenous origins of Korean democracy.